2019
DOI: 10.1016/j.envres.2018.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth in relation to the bisphenol A replacement, bisphenol S, and other phenols and parabens

Abstract: Introduction: Preterm birth continues to be a significant public heath concern and is a leading cause of perinatal and infant mortality. Environmental exposures to phenols and parabens are suspected to potentially contribute to the pathology of preterm birth, yet limited human studies have characterized the extent to which these toxicants are associated with birth outcomes. Methods:We examined the associations between phenols, parabens, and preterm birth, within pregnant women who were recruited early in gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 58 publications
3
34
1
Order By: Relevance
“…When focusing on spontaneous preterm birth, four toxicants (2,4-DCP, 2,5-dichlorophenol [2,5-DCP], triclosan [TCS], and 1-PHE) were associated with decreased odds (Supplementary Data 1B). Similar directions of associations were observed in a previous analysis of these phenols in the larger LIFECODES cohort as well 25 . Modeling gestational age at delivery revealed three phthalate metabolites (MEHHP, MEOHP, and MECPP) associated with decreased gestational age at delivery (Fig.…”
Section: Resultssupporting
confidence: 87%
“…When focusing on spontaneous preterm birth, four toxicants (2,4-DCP, 2,5-dichlorophenol [2,5-DCP], triclosan [TCS], and 1-PHE) were associated with decreased odds (Supplementary Data 1B). Similar directions of associations were observed in a previous analysis of these phenols in the larger LIFECODES cohort as well 25 . Modeling gestational age at delivery revealed three phthalate metabolites (MEHHP, MEOHP, and MECPP) associated with decreased gestational age at delivery (Fig.…”
Section: Resultssupporting
confidence: 87%
“…When focusing on spontaneous preterm birth, five toxicants (2,4-DCP, 2,5-dichlorophenol [2,, triclosan [TCS], 9hydroxyphenanthrene [9-PHE], and 1-PHE) were associated with decreased odds (Supplemental Figure 2). Similar directions of associations were observed in a previous analysis of these phenols in the larger LIFECODES cohort as well 25 . Expectedly, modeling gestational age at delivery revealed that the same phthalate metabolites (MEHP, MEHHP, MEOHP, and MECPP) that were suggestively associated with preterm birth were also suggestively associated with decreased gestational age at delivery (Figure 2).…”
Section: Associations Between Exposures and Outcomessupporting
confidence: 87%
“…One of the most debatable issues of PBs and TCS exposure is the risk that may arise for both the mother and the infant. There are animal studies that claim preterm birth or miscarriage after animals’ exposure to PBs and/or TCS [ 46 , 47 ]. Although, this refers to animals, which means to a little different organisms, this fact raises concerns about human pregnancies and the effects that exposure to these substances would cause.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been proved that both TCS and PBs are inversely associated with thyroid hormones (T3, T4, TSH) [ [48] , [49] , [50] ], a fact that is a little bit concerning considering that these hormones define also infant’s hormones system. Except for the aforementioned, PBs are also negatively associated with maternal blood pressure [ 51 ] and EtPB has been strongly associated with preterm birth [ 47 ]. TCS is associated with maternal blood pressure [ 52 ].…”
Section: Discussionmentioning
confidence: 99%